(untitled) (University of Khartoum Journal of Agricultural Sciences, 2025)
Fourteen sugarcane (Saccharum spp.) genotypes wereevaluated for resistance to the smut fungus (Ustilago scitaminea H.Sydow) disease of sugarcane in a field trial for two consecutive seasons(2006/07 and 2007/08) at Guneid, Sudan. The commercial cultivars CO527, CO 997 and CO 6806 were used as checks. The setts were inoculatedartificially by two methods: (a) the Taiwanese pin-prick method (TPPM)and (b) dipping method (DM). Data were analyzed by the weighedcomplete linkage cluster algorithm (CLINK). The results showed that the17 genotypes tested could be grouped into 4 clusters in DM and 5 clustersin TPPM. In both categories, resistance was weakest in cluster I andstrongest in cluster IV in DM and cluster V in TPPM. The resistancecharacters also gradually increased from cluster I to IV and cluster I to Vin DM and TPPM, respectively. Meanwhile, on the conventional scale, 10genotypes were rated as highly resistant or having resistant reactionssimilar to those of the resistant checks CO 6806 and CO 997. They can,thus, be propagated in commercial fields. Two genotypes; namely, D9227 and FR 9973, had smut grades of S5 corresponding to mediumsusceptible reaction type and are considered unstable and consequentlynot suitable for further propagation. Another two genotypes, FR 99204and FR99314, were rated between highly resistant and resistant and thecluster discrimination identified these genotypes as suitable, due to astrong bud resistance, and can thus be used. Also, all the 10 resistantgenotypes were classified as resistant by the clustering method and weregrouped in clusters III and IV in DM and clusters III, IV and V in TPPM.